On characteristic functions of operators on equilateral graphs - Taystruk, O.; Pivovarchik, V. N. (Methods of Functional Analysis and Topology, 2012)
Known connection between discrete and continuous Laplacians in case of same symmetric potential on the edges of a quantum graph is used to construct characteristic functions of quantum graphs and to find some parameters of graphs using spectra of boundary value problems.